Business Analysis for Enlargement of Catfish (Pangasius sutchi) in a Pool in Padang Mutung Village Kampar District Kampar Regency of Riau Province - Lubis, Rahmatika; Bathara, Lamun; Warningsih, Trisla (Jurnal Perikanan dan Kelautan, 2020)
This research was conducted in November 2019 in Padang Mutung Village, Kampar District, Kampar Regency, Riau Province. This research aimed to analyze total investment, receipts, profit, and the feasibility of an enlargement business of Catfish in Padang Mutung Village, Kampar District, Kampar Regency, Riau Province. The method used is a survey method, determining the respondents using the census method. The results showed the average investment on a small scale is IDR. 210,793,000, on a medium scale is IDR. 270,026,250, on a large scale is IDR. 772,559,000. The average receipts on a small scale is IDR. 213,000,000 with the profit is IDR. 46,820,925, on a medium scale is IDR. 270,000,000 with the profit is IDR. 62,248,187, on a large scale is IDR. 892,500,000 with the profit is IDR. 139,979,375. This catfish enlargement business is feasible to be continued, based on RCR>1, FRR>bank interest rates and PPC value ranging from 3.78 to 6.78.